Design estratégico para pequenos negócios: proposta de redesenho do programa transformando meu serviço - Villarinho, Gabriela Carneiro Monteiro Paiva (Universidade do Vale do Rio dos Sinos, 2016)
Researches about the processes that promote innovation in the Service sector are crucial, considering the diversity of natures of segments that constitute this group of enterprises. This need is reinforced by the visible growth of this sector in the last years, reaffirming the importance of the activity in the economy. Therefore, design thinking has been considered an adequate approach, for engaging interactions development process rather than being concerned only with the final result. Thereby, design can adapt itself and respond to the different needs of small businesses in developing new services. This study investigates the critical success factors of the program Transformando meu Serviço, joint realization of UNISINOS and SEBRAE/RS, which helped nine small businesses in constructing or transforming a service. This research was developed by a case study with content analysis of the material produced during the workshop and data collection by interviews, focus groups and field diaries. By the end of the study, eight hypotheses were formulated, that have been translated into a proposal to recast the program Transformando meu Serviço, consisting in a preliminary questionnaire to be answered by the owner of the business, basic premises for implementation of the programme and a set of directions for the actors of the process.
Keywords: Design estratégico; Design thinking; Empreendedorismo; Pequenos negócios; Strategic design; Entrepreneurship; Small and medium business; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial